Notas acerca de la sobreproducción de arte, la posfotografía y lo digital - Roncoroni Osio, Umberto (2014)
This essay discusses the post-photography statement in terms of its most important concepts: the author, poiesis as a prescription of meaning, recycling as artistic strategy, serendipity and art’s social and political struggle. Even sharing the fundamentals of Fontcuberta’s decalogue, it is necessary to underline that problems of overproduction cannot be actually solved. Something more is needed: a structural relationship with postmodern philosophical problems; a suppression of unrecognized modern aesthetic foundations; and a deeper analysis of the properties of digital media and technologies. Moreover, the photographic point of view is too narrow to grasp all the aesthetic consequences of the described artistic postmodern conditions. As a conclusion, some different hypotheses concerning uncommon theoretical and artistic practices are discussed.